The high-speed rotorcraft unmanned aerial vehicle path planning based on the biogeography-based optimization algorithm. (May 2019) - Song, Jia; Zhao, Mingfei; Yang, Erfu; Lin, Jiaming
A three-dimensional path planning method based on the biogeography-based optimization algorithm is presented for high-speed rotorcraft unmanned aerial vehicle which has a maximum speed of 20 m/s. In this study, a novel exponential artificial potential field is used to prevent saturation, for its peculiarity of smoothness and boundness. Several parameters, which can make a large influence to the result of path planning, are picked out and used to improve the process of planning. Biogeography-based optimization algorithm is first used to optimize the parameters of artificial potential fields, for its best performance in stability and speed. The algorithm has good stability and fast operation speed, which can realize the global path planning of multi-rotor aircraft well, verified by the simulation results.